Internal Perspectives on Visual Identities in Higher Education: A Case Study of Top-Ranked Universities in Indonesia [version 1; peer review: 2 approved] - Luqman Lee; Rabendra Yudistira Alamin; Syarifa Hanoum; Ellya Zulaikha; Putri Dwitasari (F1000Research)
Background The neglect of visual identity (VI) at the organizational level within higher education institutions (HEIs) has become a critical issue, while previous studies over the past decade has focused on HEI branding and reputation. This creates a potential gap in understanding HEI branding processes. Thus, this study aims to explore the relationship between VI and HEI reputation by integrating the Expressiveness Quotient (EQ) and experiential brand meaning at the organizational level. Method Using a qualitative case study approach, the study involves semi-structured interviews with 29 employees from five top-ranked universities in Indonesia. Furthermore, it analyzes the integration of experiential brand meaning across the stages of awareness, interpretation, appropriation, and communication, alongside the EQ framework to assess how visual identity impacts visibility, distinctiveness, transparency, authenticity, and consistency. Result The findings indicate that visual identity significantly influences perceptions of institutional identity and reputation. Effective management of visual identity elements enhances competitive advantage in academia and aligns internal stakeholder perceptions with external branding, which is essential for a cohesive organizational identity. Conclusion This study emphasizes the strategic importance of visual identity in enhancing institutional reputation and provides a model for universities aiming to strengthen their reputational power through effective visual identity management. The study also reveals strong awareness and acceptance of brand identity.